(untitled) (Italian Journal of Public Health, 2008)
Background: Multiple-language versions of the same psychometric instrument are increasingly needed, but simply translating an English version word-to-word into another language is not adequate to account for linguistic and cultural differences. Our aim was to validate an Italian version of the Axis II of the Research Diagnostic Criteria for temporomandibular disorders (RDC/TMD) and to test its reproducibility in order to use this important diagnostic instrument in Italian patients. Methods: The original English-language version was translated and culturally adapted for Italian-speaking people, back-translated to English and then tested on 68 subjects: 34 TMD patients and 34 healthy subjects. Internal consistency was assessed by calculating the Cronbach coefficient alpha for the entire scale in the two samples. The reproducibility of the domains was assessed with the use of the Spearman-Brown test-retest reliability test, Wilcoxon matched pair test, Sign test and 2x2table Chi Square test according to the data types. Correlation of the initial and test-retest scores of the Axis II was measured with the Spearman rank correlation coefficient as an additional measure of reproducibility. Results: The Italian version of Axis II has a good reproducibility; the internal consistency (measured with the Cronbach coefficient alpha) of the overall final questionnaire was excellent: 0.95. Conclusions: The Axis II Italian version appeared reliable and it could be useful to assess TMD patients and to standardize the data acquisition in this relevant and common disease.